Promising Predictors of preeclampsia Creatinine Kinase and Tyrosine Kinase 1 in preeclamptic pregnant women in the third trimester of pregnancy - Edebiri O.E; Nwankwo A.A; Akpe P. E; Mbanaso E.I; Onwuka K. C; Ohiwerei W.O; Omende K (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The potential of cardiac markers in predicting preeclampsia, such as Creatinine Kinase (CK) and Tyrosine Kinase 1 (TK1), has emerged as promising due to their involvement in the pathophysiology of this pregnancy complication. Preeclampsia is characterized by hypertension and organ dysfunction, and it can lead to significant maternal and fetal morbidity if not detected early. Early identification of preeclampsia is critical for preventing severe complications, and biomarkers like CK and TK1 can provide valuable insights. This study aimed to investigate the role of CK and TK1 as potential predictors of preeclampsia in the third trimester of pregnancy. Forty (40) consenting pregnant women were recruited from St. Philomina Catholic Hospital, Edo State, Nigeria. Participants were divided into two groups: twenty (20) normotensive pregnant women and twenty (20) preeclamptic pregnant women in their third trimester. Blood samples were collected and processed using a bucket centrifuge at 2500 RPM for 10 minutes, and plasma was stored frozen for further analysis. Tyrosine Kinase 1 was analyzed by fluorescence immunoassay, and Creatinine Kinase was measured using a spectrophotometric method. Data obtained were analyzed using GraphPad Prism 9, with results expressed as mean ± SEM. Statistical significance was set at a P-value of ≤ 0.05. The study found a statistically significant increase in the levels of both CK and TK1 in preeclamptic women compared to normotensive controls. These findings suggest that CK and TK1 could serve as predictive biomarkers for identifying and monitoring preeclampsia, aiding in early diagnosis and timely interventions